Pengaruh Kinerja Keuangan terhadap Kebijakan Dividen dengan Ukuran Perusahaan sebagai Moderasi: Perusahaan Sektor Non-Keuangan yang Terdaftar di BEI Periode 2020-2023 - Jamhari Ramdani Mukti; Rico Wijaya Z; Fredy Olimsar (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The Indonesia Stock Exchange (IDX) provides public access to investment. Investors can invest in various companies through publicly listed securities using capital market processes to obtain returns and dividends. To obtain returns and dividends, investors first read the company's financial statements to avoid losses. Aiming to provide empirical evidence, this study analyzed non-financial corporations listed on the IDX between 2020 and 2023 to determine the impact of financial performance on dividend policy, along with company size as a moderating variable. This research employed a quantitative approach and purposive sampling for data selection, which was updated in line with predetermined indicators. Over four years, 147 different companies served as study samples. The study used warpPLS 7.0 as a data analysis tool and combined outer and inner models to evaluate independent variable hypotheses and moderating hypotheses. The study found that liquidity plays a role in dividend policy, profitability plays a role in dividend policy, activity plays a role in dividend policy, and only solvency does not play a role in dividend policy. It was also found that company size does not moderate the relationship between liquidity and dividend policy, but it does moderate the relationship between profitability and dividend policy. Company size also does not moderate the relationship between activity and dividend policy, and does not strengthen the relationship between solvency and dividend policy.